The Prison Memoirs of an Inebahti Veteran: Serguzestname-i Hindi Mahmud - (:unkn) unknown (ISAM, 2011)
This article introduces a memoir called the Serguzestname. This masterpiece of the genre presents the experiences and observations of a certain Hindi Mahmud during the years that served Sultan Selim II as secretary, 'qapijibashi', and 'muteferriqa.' Particularly important is its description of the Battle of Lepanto (1571), in the course of which the author was captured and enslaved by the Holy Alliance forces. Until recently this memoir was presumed lost. It cover Hindi Mahmud's experiences during the four year period in which he was imprisoned in Messina, Napoli and Rome in Sicily and Italy, his opinions about the Papacy and Vatican, the ceremonies of accession and funeral ceremonies, the religious life of prisoners of war, prison conditions etc. The information it provides is a valuable source for students of cultural history. In a second work, the comprehensive Qisas-i Enbiya written in 1579, Hindi Mahmud stated that his Serguzestname consisted of 8000 verses. But the only known surviving manuscript of the work, that preserved in Edirne's Selimiye Manuscript Library, is missing 1113 verses. Too date, the Serguzestname is the earliest captivity memoir ('esaretname') from the Ottoman period. Accordingly, even without its missing section, the Serguzestname is an extremely important document for the academic world.
Keywords: Hindi Mahmud; Battle of Lepanto; Serguzestname; Prison; Selim II